Rancangan Pembelajaran Flipped Classroom Untuk Mata Kuliah Persepsi Desain dan Pesan - Hana Alodianada; Retno Widyaningrum; Kunto Imbar Nursetyo (Universitas Negeri Jakarta, 2019)
This development research aims to produce a flipped classroom learning in the form of a RPKPS as a guideline for implementing flipped classroom learning in PDP courses at the State University of Jakarta in Educational Technology Program. This development research was carried out by following the Rapid Prototyping development model procedure, namely Assess Needs & Analyze Content 2) Set Objectives, 3) Construct Prototype, 4) Utilize Product, 5) Installation & Maintenance. Evaluation of this product development research is done through Expert Review. The step of expert review involved 1 subject expert and 2 learning design experts. The average value obtained from subject expert is 3,48 which means it’s very good, from learning design expert is 3,21 which means it’s good. The average value obtained from another learning design expert is 3,24 which means it’s good. From these results it can be concluded that the flipped classroom learning design for Learning and Design Perception Course is good rated.